Analysis of the youth labor market in the Republic of Kazakhstan in the context of global challenges - S. A. Kaliyeva; E. K. Buitek; M. K. Meldakhanova (Экономика: стратегия и практика, 2020)
The purpose of research paper is to analyze the structure of youth employment for 2014-2018, determine the impact of the pandemic on the development of national and regional labor markets, highlight the problems of imbalance in the youth labor market, identify the peculiarities of internal migration of the young population in the labor market of Kazakhstan. Methodology. The research methodology includes general scientific, private, empirical and theoretical research methods. Methods and tools of statistical analysis, comparative, structural, and factor analysis were used in the preparation of the article. Methods of tabular and graphical representation of data are used as statistical tools. Originality/value of the research - Ensuring youth employment has an impact on the country’s economic growth and socio-economic modernization and is considered as one of the most important factors determining the quantitative and qualitative parameters of the total labor force reproduction. Findings. Authors suggest measures to improve the situation of young people in the labor market of Kazakhstan.